Iranian Tribes and Their Political and Social Role in Iran in Lorimer's Gazetteer of the Arabian Gulf (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This research aims to identify Iranian tribes and their significant role in Iran, and to understand and manage diversity, as described in the book Gazetteer of the Arabian Gulf by researcher and historian John Gordon Lorimer and his book "Gazetteer of the Gulf." It also attempts to arouse interest and draw the attention of those interested in social and historical issues to the need to study these tribes, given their importance in the lives of individuals and society. The research also aims to identify the types of tribes and their geographical locations, as well as to identify the ruling families of these tribes and their political role in Iran.